Startup valuation sensitivity to liquidation preferences in closed investment rounds - Mannis, José Renato (2025)
Startup valuations are often derived from the price per share paid by the most recent investor in a funding round. However, in venture capital contracts, clauses such as liquidation preferences can create a valuation gap between the nominal valuation and the economic reality. This dissertation investigates how variations in the liquidation preference multiplier influence the gap between the post-money valuation and the fair value of a startup at exit. A structured scenario analysis model was developed to represent a staged financing process with five investment rounds, culminating in an exit event. The model assumes that only the final investor holds a liquidation preference, and that the exit occurs immediately after the last round. The scenario analysis computes a valuation gap metric dv, which compares the perceived value implied by investor payouts to the actual fair value of the company. Through a two-dimensional sensitivity analysis, the study reveals that even moderate liquidation preference multipliers (e.g., L=1.5 or 2.0) can significantly inflate perceived valuations, especially when the exit value is low. The results underscore that investor protection mechanisms, while common and often justifiable, introduce structural misalignments between nominal and economic valuation. This work contributes a quantitative framework for analyzing such valuation gaps and highlights the importance of contract structure in shaping startup financial narratives.